2000
DOI: 10.1177/1368430200033005
|View full text |Cite
|
Sign up to set email alerts
|

Collective Efficacy and Aspects of Shared Mental Models as Predictors of Performance Over Time in Work Groups

Abstract: We assessed collective efficacy (a group's judgment of their ability to perform a particular task) and some dimensions of shared mental models (models of the group structure, process and the task, that members hold in common) in student groups working on semester-long research projects. In particular, we assessed the extent to which group members had agreement and accuracy about members' past and future contributions to the group project, and agreement about the importance of various task aspects. Groups with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 45 publications
4
88
0
4
Order By: Relevance
“…It is nonetheless important to note that collective efficacy is a team level construct rather than an aggregate of individual levels of self-efficacy (Zaccaro et al, 1995). Collective efficacy leads a team to establish higher goals, to exert more effort in the pursuit of these goals and to demonstrate greater persistence in case of any failure or negative feedback (e.g., Peterson, Mitchell, Thompson & Burr, 2000) which aligns with Proposition 1a). Marks (1999), has also reported improved inter-member coordination in teams with high efficacy with beneficial consequences for performance of especially novel tasks.…”
Section: Proposition 4 Motivational States -Collective Efficacymentioning
confidence: 82%
See 1 more Smart Citation
“…It is nonetheless important to note that collective efficacy is a team level construct rather than an aggregate of individual levels of self-efficacy (Zaccaro et al, 1995). Collective efficacy leads a team to establish higher goals, to exert more effort in the pursuit of these goals and to demonstrate greater persistence in case of any failure or negative feedback (e.g., Peterson, Mitchell, Thompson & Burr, 2000) which aligns with Proposition 1a). Marks (1999), has also reported improved inter-member coordination in teams with high efficacy with beneficial consequences for performance of especially novel tasks.…”
Section: Proposition 4 Motivational States -Collective Efficacymentioning
confidence: 82%
“…Watson, Chemers and Preiser (2001) showed that collective efficacy can be based on perceptions of individual member proven efficacy in newly formed (e.g., sports) teams, but will eventually evolve its own supra-ordinate reality (with a correspondingly weakening impact of self-efficacy on team performance). Finally there is also some evidence showing that collective efficacy early on in a team process can furnish the development of shared mental models (Peterson et al, 2000) suggesting that shared mental models may in part mediate the impact of collective efficacy on performance.…”
Section: Proposition 4 Motivational States -Collective Efficacymentioning
confidence: 99%
“…A third limitation is the use of a survey to capture task processes. Although this is a commonly used approach in assessing shared mental models (Peterson, Mitchell, Thompson, and Burr, 2000;Yoo and Kanawattanachai, 2001;Levesque, Wilson, and Wholey, 2001), surveys have distinct disadvantages. For example, they present issues in the researcher's voice, not the informant's.…”
Section: Discussionmentioning
confidence: 99%
“…Again, in order to stay on the most general level, collective efficacy is the term used here to describe the psychological outcome of adaptation. Collective efficacy reflects the group's anticipation that it will do well on a particular task (Peterson et al, 2000). While it is widely accepted that a higher level of collective efficacy will result in a high level of task execution, our model also reflects the other direction of this relationship, namely that a high level of task execution will result in an increase in collective efficacy.…”
Section: Adaptation As An Outcomementioning
confidence: 99%